Membership accession in the African Union: The relationship between enforcement and compliance, and the case for differential membership. Issue 1 (2nd January 2017) - Boateng, Oheneba A.
ABSTRACT: It is argued in this paper that the level of non-compliance is high in the Organisation of African Unity/African Union in part because the organisation failed to institute and enforce strict membership accession conditionalities. Across the life of the organisation, this has resulted in non-compliance, mainly the non-payment of dues and non-implementation of policies. This position adds a historical dimension to arguments that identify weak economic capacity and the lack of political will as the main sources of non-compliance. It also supports the thesis that the enforcement of strict accession rules prepares states to perform their obligations and sets them up to receive benefits from the group. In 2002, Africa's continental body changed its mandate from liberation to integration. Since integration requires the strict enforcement of accession rules, the paper suggests that the organisation proceed by choosing differential membership to align the behaviour of its members to their obligations.